Abdominal hysterectomy due to uterine rupture causing bilateral ureterovaginal fistula: A rare case report - Amitayu Jana; Krishnendu Maiti (Annals of Medical Science and Research)
Ureterovaginal fistula (UVF) is defined as abnormal communication between ureter and vagina. Although documented after radical hysterectomy, post radiation and retained pessary incidence of bilateral UVF is still very rare. We have documented a case report of a multipara woman presented with persistent urinary leakage following an emergency hysterectomy for obstructed labor. After evaluation with imaging there was bilateral hydroureterophrosis with dense purulent collection mixed with contrast in the vesicular area with lower end of ureter draining in the vaginal vault with preserved renal function. During exploration both ureters were dilated. Instillation dye in both ureters showed extravasation in vagina. After ligating distal ends modified Lich-Gregoir technique done over double J (DJ) stents. DJ removed after 3 months. Bilateral UVF is only 5%–10% of all ureteric injury. Aggressive blind clamping, excessive hemorrhage, distorted anatomy, malignancy and surgeons experience play a crucial role. Obstetric cause is the prime factor. Preventing measures like proper screening of antenatal patients, early detection of high-risk pregnancy, supervised caesarean section should be taken to avoid ureteric injuries